Respuesta :

Answer: x = 1 or x = -3

Ok done. Thank to me :3

Ver imagen silirobert15

Answer:

Step-by-step explanation:

Completing square:

3 + x = x² + 3x

x² + 3x = x + 3

Step 1: Subtract 'x' from both sides

x² + 3x - x = 3

x² + 2x = 3

Step 2: Divide the coefficeint of x by 2 and square the result

2 ÷ 2 = 1

1² = 1

Step 3: Now add 1 to both the sides

x² + 2x + 1  = 3 + 1

x² + 2x + 1 = 4

The LHS of the equation is in the form a² + 2ab + b² = (a +b)²

(x + 1)² = 2²

Take square root,

x + 1 = ± 2

x + 1 = 2      ;x + 1 = -2

     x = 2 - 1 ;     x  = - 2-1

      x = 1     ;     x = -3

Solution: x = 1,-3